Mir-let-7i-5p as a novel regulator of MYC gene expression in acute myeloid leukaemia - Ezalia Esa,; Wan Muhammad Farhan Syafiq Wan Mohd Nor,; Elsa Haniffah Mejia Mohamed,; Lim, Wei-Yue; Zubaidah Zakaria,; Yuslina Mat Yusoff,; Pau, Ivyna Ni Bong; Pung, Yuh-Fen; Noor Atiqah Fakharuzi,; Shamsul Mohd Zain, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Acute myeloid leukaemia (AML) is a severe bone marrow malignancy with a high mortality rate. Recent advancements in high throughput technology and bioinformatics have facilitated the identification of microRNAs (miRNAs) involved in the pathogenesis of AML. This study aimed to investigate the potential role of MicroRNA-let-7i-5p (miR-let-7i-5p) in the progression of AML. MiR let-7 family has been widely utilised as a tumour inhibitor, suppressing its expression in several types of human cancer. Hence, dysregulation of miR-let-7i-5p is critical to cancer progression. However, the role of miR-let-7i-5p in AML remains unclear. Using the Gene Expression Omnibus (GEO) database, the expression of miR-let-7i-5p in AML patients was investigated. The role of miR-let-7i-5p and its potential target genes in AML was examined using bioinformatic tools. Subsequently, the effect of miR-let-7i 5p was assessed through transfection, followed by the analysis of target gene expression using RT-qPCR. Further investigations employed the MTT and cell cycle assays on the effects of miR-let-7i-5p on AML cell proliferation and cell cycle. According to the GEO database, miR-let-7i-5p was significantly downregulated in AML patients compared to controls. AML development has been associated with miR-let-7i-5p by KEGG pathway analysis. Bioinformatics suggested that miR-let-7i-5p targets MYC in AML cells. Transfection of miR-let-7i-5p into AML cell lines decreased MYC expression, suggesting MYC regulates AML progression. However, MTT and cell cycle assays showed no significant effect of miR-let-7i-5p on AML cell proliferation and cell cycle, indicating the potential involvement of miR-let-7i-5p in alternative pathways in AML pathogenesis. The study highlights the potential significance of miR-let-7i-5p in regulating AML progression.